1972
DOI: 10.2136/sssaj1972.03615995003600010055x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Concretions from Selected Soils of the Inner Bluegrass Region of Kentucky

Abstract: Total iron and manganese was determined on concretions and soil samples by X‐ray emission. Soils studied included Maury, Mercer, and Lawrence, which are well‐drained, moderately well‐drained and somewhat poorly‐drained, respectively. Iron‐Manganese concretions were observed in all horizons, with a maximum of 46% by weight in a Maury C horizon. The Fe/Mn ratios decreased with increasing concretion size. This decrease was largely due to increased Mn content associated with the larger size concretions. Further an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
6

Year Published

1979
1979
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 0 publications
0
7
0
6
Order By: Relevance
“…Variations in the original deposition and subsequent redistribution of loess provide an additional level of spatial structuring. In addition to the silt cap versus no silt cap distinction, soils with fragipans are found only in the former – though the presence of similar Fe/Mn concretions in other soils (though not sufficient to result in a fragipan; Phillippe et al, 1972) suggests that aeolian silt inputs have been important even when no silty mantle over weathered limestone is discernible, as the limestone contains minimal Fe and Mn.…”
Section: Interpretation Of Inner Bluegrass Soil Landscapesmentioning
confidence: 99%
“…Variations in the original deposition and subsequent redistribution of loess provide an additional level of spatial structuring. In addition to the silt cap versus no silt cap distinction, soils with fragipans are found only in the former – though the presence of similar Fe/Mn concretions in other soils (though not sufficient to result in a fragipan; Phillippe et al, 1972) suggests that aeolian silt inputs have been important even when no silty mantle over weathered limestone is discernible, as the limestone contains minimal Fe and Mn.…”
Section: Interpretation Of Inner Bluegrass Soil Landscapesmentioning
confidence: 99%
“…When the soil dries out, Fe(II) and Mn(II) oxidize and precipitate, forming new metal oxides. Macroscopic characteristics of nodules and the distribution of Fe and Mn oxides within nodules have been the subject of several studies (Cescas et al, 1970;Phillippe et al, 1972;Liu et al, 2002a;Cornu et al, 2005). With the development of X-ray microprobe analytical techniques, heavy metals naturally sequestered by Fe-Mn nodules have been studied in detail (Manceau et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The cementing agents for Fe-Mn concretions are Fe and Mn oxides. Therefore, the concretionary material is characterized by a greater concentration of Fe and Mn oxides than the surrounding soil matrix (Barnhisel et al 1969;Phillippe et al 1972;Rhoton et al 1993). It also differs from the surrounding soil matrix by containing less SiOv Schwertmann and Fanning (1976) found that Mn and Fe are not evenly distributed in all concretions found within a given soil horizon or even within a given concretion.…”
Section: Introductionmentioning
confidence: 99%
“…Manganese content is usually related to concretion size, with larger concretions containing more Mn and lower Fe/Mn ratios. Also, dark-colored concretions are generally higher in Mn content than lighter-colored concretions (Phillippe et al 1972), but color, shape and hardness may differ among different soils. Concretions found in the better-drained soils of loess hydrosequences in Bavaria were usually rustycolored with a blackish interior, irregular in shape and medium in hardness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation